A computational approach to quantifying miscounting of radiation-induced double-strand break immunofluorescent foci - Samuel P. Ingram; John-William Warmenhoven; Nicholas T. Henthorn; Amy L. Chadiwck; Elham E. Santina; Stephen J. McMahon; Jan Schuemann; Norman F. Kirkby; Ranald I. Mackay; Karen J. Kirkby; Michael J. Merchant (Communications Biology, 2022)
PyFoci is a tool that simulates distributions of fluorescently labeled DNA double-strand break marker protein foci and allows the estimation of miscounting under different radiation types, doses and microscopy settings.